Study on the corrosion and wear behaviors of cylinder liner in marine diesel engine burning low sulfur fuel oil. (May 2023) - Hou, Xianbin; Wang, Yuxin; Dai, Leyang; Yang, Yuhao; Du, Jinhong; Wang, Yongjian; Wan, Hong
Highlights: The corrosion and wear behaviors of cylinder liner in marine diesel engine under different simulated conditions were investigated. FeSO4, Fe3 O4, Fe2 O3, FeO and FeS were the products of chemical corrosion and electrochemical corrosion of cylinder liner in marine diesel engine burning low sulfur fuel oil. The interaction between corrosion and wear of cylinder liner in marine diesel engine burning low sulfur fuel oi were studied. There was an obvious interaction between corrosion and wear, corrosion and wear promoted each other and jointly accelerated the loss of cylinder liner in marine diesel engine burning low sulfur fuel oil. Abstract: The use of low sulfur fuel oil causes the abnormal corrosion and wear of cylinder liner in marine diesel engine. Marine diesel engine cylinder liner material and marine diesel engine cylinder oil were taken as test material and test oil, respectively. Static immersion test, electrochemical test and corrosion wear tests were carried out by simulating the different working conditions of marine diesel engine. To analyze the corrosion behaviors of cylinder liner in marine diesel engine, its corrosion mass loss, polarization curve, electrochemical impedance plots, surface morphology and composition distribution were examined. Also, the electrochemical corrosion volume loss and friction volume loss were analyzed quantitatively to reveal the mechanism of interaction between corrosion and friction. The results showed that the severity of corrosion caused to cylinder liner varied under different working conditions of marine diesel engine, with the water, oxygen and acid in cylinder oil as the main causes for the corrosion of cylinder liner. There was an interaction occurring between the corrosion and wear of cylinder liner in marine diesel engine, and the interaction volume loss ΔV between the corrosion and wear to the total wear volume loss VT (ΔV/VT ) was 13.9%. The promotion volume loss rate of wear on corrosion Vmc was about 3.86% of the total volume loss VT (Vmc /VT ). The promotion volume loss rate of corrosion on wear Vcm was about 10.02% of the total volume loss VT (Vcm /VT ). The interaction between the corrosion and wear was an important factor affecting the wear resistance and corrosion resistance of marine diesel engine cylinder liner. This study provides theoretical reference for suppressing the corrosion and wear behaviors of cylinder liner in the marine diesel engine burning low sulfur fuel oil.